Accelerated In Vitro Propagation of Sweetpotato Clones (Ipomoea batatas L.) - Vollmer, R.; Espirilla, J.; Sánchez, J.C.; Arroyo, L.; Flores, G.; Anglin, Noelle L.; Kreuze, Jan F.; Ellis, David (Springer, 2022)
Fast and reliable propagation of plant material is an important need in different stages of breeding programs and production systems. In vitro propagation ensures that pathogen- and virus-free plants stay phytosanitary clean over time while providing high multiplication rates. Using liquid instead of solid culture medium can reduce the interval of individual propagation cycles and contributes to speeding up of the process (1.5–2.5 times), especially during the initial growth phase of the plants. Sophisticated immersion systems have been developed for many plant species, but they are difficult to apply when hundreds or thousands of different genotypes are propagated simultaneously. Additionally, these systems require a high input of technical equipment, know-how and experience to avoid bacterial or fungal contamination during the propagation process. The following protocol describes a low-input suspension technique that combines the use of liquid and solid medium, and permits the successful propagation of genetically diverse sweetpotato genotypes [Ipomoea batatas (L.) Lam.] with a high multiplication rate. As sweetpotato is an important staple crop in low-income/technology countries of Africa, Asia, and South America, the described method may find valuable application for the breeding programs in these regions.